Mechanical properties of dense mycelium-bound composites under accelerated tropical weathering conditions - Xin Ying Chan (Nature Portfolio, 2021)
Abstract Mycelium, as the root of fungi, is composed of filamentous strands of fine hyphae that bind discrete substrate particles into a block material. With advanced processing, dense mycelium-bound composites (DMCs) resembling commercial particleboards can be formed. However, their mechanical properties and performance under the working conditions of particleboards are unknown. Here, we show how weathering conditions affect the DMC stress and elastic modulus. DMC was made using Ganoderma lucidum mycelium grown on a substrate of sawdust and empty fruit bunch. The DMC was then subjected to weathering under tropical conditions over 35 days and tested under flexural, tensile, and compressive loading with reference to international standards. After exposure to specified weathering conditions, the maximum stress in flexure, tension, and compression decreased substantially. The addition of a protective coating improved the resistance of DMC to weathering conditions; however, the difference between coated and uncoated samples was only found to be statistically significant in tensile strength.